2015 IEEE 39th Annual Computer Software and Applications Conference 2015
DOI: 10.1109/compsac.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Mobile Devices in Higher Education: Pilot Project

Abstract: Reflecting latest trends in higher education, social networks and mobile devices have been detected to be important tools. Collecting the appropriate data the main objective of the research was to consider whether mobileassisted learning could be used within the faculty. The survey monitoring their use for private and education purposes was held at the Faculty of Informatics and Management, University of Hradec Kralove, Czech Republic. Data were collected by the questionnaire from the sample of 203 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Isamiddinovna (2019) indicated that MALL is considered a promising technology approach for learning a foreign language. MALL is different from traditional learning because learners can conveniently interact with mobile devices anytime and anywhere (UNESCO, 2013;Simonova, 2015). There are a variety of mobile applications which provide learners with useful and informative knowledge.…”
Section: Mobile-assisted Language Learning (Mall)mentioning
confidence: 99%
“…Isamiddinovna (2019) indicated that MALL is considered a promising technology approach for learning a foreign language. MALL is different from traditional learning because learners can conveniently interact with mobile devices anytime and anywhere (UNESCO, 2013;Simonova, 2015). There are a variety of mobile applications which provide learners with useful and informative knowledge.…”
Section: Mobile-assisted Language Learning (Mall)mentioning
confidence: 99%
“…They stated that they were happy to be able to access the course materials and to communicate with their teachers and friends wherever and whenever they wanted, as well as to get help from social networks to prepare for their exams and their homework or projects. Some other research shows that social networks support informal learning (Alcantar, Ballesteros, Torres, Padilla, and Barajas, 2016;Alkan and Bardakçı, 2017;Al-Mukhaini, Al-Qayoudhi, and Al-Badi, 2014;Asberg, 2013;Buzzetto-More, 2012;Chvanova, Khramova, Pitsik, and Hramov, 2016;Clothey, 2016;Dere, Yücel, and Yalçınalp, 2016;Dhanhani, Mizouni, Otrok, and Rubaie, 2015;James, 2014;Klimova and Poulova, 2015;Komninou, 2018;Lavy, 2015;Messner, 2009;Mora, Pont, Casado, and Iglesias, 2015;Moolenaar and Daly, 2012;Pettenati and Ranieri, 2006;Rivero, 2011; Sá nchez-Gómez, Iglesias-Rodrí guez, and Garcí a-Peñalvo, 2017; Schachter, 2011; Simonova and Poulova, 2015;Wang, Chen and Liang, 2011).…”
Section: Social Network As a Learning And Teaching Environmentmentioning
confidence: 99%
“…Social networks and mobile devices are major tools for reflecting the latest trends in higher education. Simonova and Poulova [22] collected relevant and appropriate data for statistics on the types and access frequencies of 19 social networks and the ownership and purposes of use of 12 kinds of mobile devices; the results showed that students have been fully equipped with mobile devices and use them for private purposes, and a high learning efficiency has been achieved. Amaratunga and Ranasinghe [23] created a mechanism to exploit the inherent but haven't been fully utilized functions of mobile devices with a content format specifically designed to maximize opportunistic educational content delivery and take it as a means of disseminating basic educational content.…”
Section: Introductionmentioning
confidence: 99%